Analgesic nephropathy - Jampong, Malinporn; Satirapoj, Bancha (Journal of the Nephrology Society of Thailand, 2022)
Analgesic nephropathy is a chronic kidney disease leading to end stage renal disease that can be prevented or often arrest renal progression. The term usually refers to kidney injury induced by excessive and long use of analgesics or analgesic mixtures, especially combinations including phenacetin. The incidence of disease is uncertain because a definite diagnostic criterion is rarely made. Renal pathologic findings are characterized by renal papillary necrosis and chronic interstitial nephritis. This condition is common found among middle-aged women in around 50 to 80% of females. Commonly used drugs associated with analgesic nephropathy include aspirin, salicylamide and acetaminophen. The main mechanisms of kidney injury are accumulation of N-acetyl-p-benzoquinoneimine, the reactive metabolite of acetaminophen producing lipid peroxides and arylation of tissue proteins and renal medullary ischemia. Clinical manifestations of analgesic nephropathy are generally nonspecific. It constitutes a slowly progressive form of kidney injury with and without sterile pyuria. Some patients develop renal colic from necrotic renal papillae with obstructive uropathy. Diagnostic criteria have been defined based on history of analgesic consumption and renal computed tomography scanning without contrast. The observation of decreased renal mass, combined with either bumpy contour or papillary calcification showed a high sensitivity and specificity for diagnosing disease. The first line of treatment is to discontinue the offending drug to prevent any further damage without specific treatment. The clinical course varies and depends mainly on the extent of renal damage. In addition to renal impairment, prolonged heavy analgesic use can lead to atherosclerotic disease and urothelial carcinoma.